Employment and Education as Risk Factors of Cataract Incidence on Patients Treated in Eye Health Centre Mataram City West Nusa Tenggara - Ni Nyoman Santi Tri Ulandari; Putu Ayu Swandewi Astuti; I Nyoman Adiputra (Universitas Udayana, 2014)
Background and purpose: The purpose of the study was to determine the risk factors of employment, education and other risk factors on the occurrence of cataracts in patients seeking treatment at Eye Health Center in the City of Mataram, West Nusa Tenggara. Methods: The study was a case-control with a sample of cases and controls, respectively amounted to 40 (1: 1). The dependent variable was patients with cataract and independent variables were: education, employment, income, diabetes mellitus, history of cataracts, smoking behavior, and exposure to smoke and sun exposure. Data were collected by means of interviews using questionnaires and tracking documents of patients’ medical records. Data analysis was performed using univariate, bivariate to determine the comparability between cases and controls and to see the crude of OR. Multivariate analyses were performed to determine the adjusted OR. Results: Four variables were found to be risk factors to the occurrence of cataracts: education, income, occupation and exposure to sunlight with each crude OR of 10.50 (95% CI: 3.39 to 32.52); 6.23 (95% CI: 2.35 to 16.51), 10.52 (95% CI: 3.56 to 31.12); and 3.11 (95% CI: 1.25 to 7.78). While diabetes mellitus, family history of cataracts, smoking behavior and exposure to smoke was not statistically proven as a risk factor for cataracts. The multivariate analysis showed that most risk factors played a role in the occurrence of cataract was employment with OR=9.81 (95% CI: 1.85 to 52.02) and education with OR=6.53 (95% CI: 1.42 to 29.92). Conclusion: Employment and education were significant risk factors to the occurrence of cataracts in patients who visited the Eye Health Center in the City of Mataram, West Nusa Tenggara.